Does Internal Quality Assurance Improve Teaching and Learning? A Systematic Review of Impact Evidence Through the 3P Lens - Abdul Kholid Achmad; Rahmat Agus Santoso; Wannaporn Siripala; Sutiah Sutiah (Universitas Muhammadiyah Mataram, 2026)
Internal quality assurance (IQA) has emerged as a central governance mechanism for teaching and learning in higher education, yet its effectiveness remains contested. Prior reviews have primarily clarified how IQA is conceptualized, while empirical evidence on its impact on teaching quality and student learning outcomes remains fragmented and uneven. This systematic review synthesizes evidence of IQA’s impact and examines how outcomes vary across macro–meso–micro contexts through the 3P lens (Purpose–People–Process). A comprehensive search was conducted in Scopus, supplemented by backward reference screening. Following PRISMA guidelines, 1,030 records were screened, 96 full-text articles were assessed for eligibility, and 43 studies were retained. Data were extracted using a structured coding framework covering study characteristics, IQA purposes, actors, processes, contextual levels (macro–meso–micro), and reported outcomes. Methodological quality was assessed using the Mixed Methods Appraisal Tool (MMAT). The synthesis combined deductive framework analysis based on the 3P model with realist-informed analysis of context–mechanism–outcome configurations to explain how different IQA arrangements generate, constrain, or moderate impacts on teaching quality and student learning outcomes. Across the included studies, IQA is most consistently associated with strengthened review routines and program-level improvement processes (e.g., curriculum renewal, assurance-of-learning/assessment loops, and governance for monitoring), whereas evidence for direct student learning outcomes is limited and frequently relies on proxy measures such as satisfaction and student evaluations of teaching. Positive impacts are more likely when IQA aligns improvement-oriented purposes with distributed actor engagement and closed-loop processes that translate evidence into action (e.g., feedback-to-action cycles), while compliance-driven configurations tend to show weaker or mixed effects. The review provides an evidence map and a testable program theory linking IQA configurations to outcomes, highlighting priority gaps for longitudinal designs and evaluation research inclusive of the Global South.